1994
DOI: 10.1029/93ja03135
|View full text |Cite
|
Sign up to set email alerts
|

Galactic cosmic ray modulation and interplanetary medium perturbations due to a long‐living active region during October 1989

Abstract: During October 1989, three very energetic flares were ejected by the same active region at longitudes 9° E, 32° W, and 57° W, respectively. The shape of the galactic cosmic ray variations suggests the presence of large magnetic cloud structures (Nagashima et al., 1990) following the shock‐associated perturbations. In spite of long data gaps the interplanetary observations at IMP 8 (near the Earth) and ICE (∼1 AU, ∼65° W) confirm this possibility for the event related to the 9° E flare; the principal axes analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
3

Year Published

1995
1995
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 15 publications
0
14
3
Order By: Relevance
“…The cosmic ray record at Earth is consistent with this picture such that only the first two shock-associated cosmic ray decreases had the signature expected for intercepting ejecta material. This same time period was also examined by Bavassano et al (1994). However, we do not agree with their conclusion that "magnetic clouds" extending at least 75 ø from the source longitude were present.…”
contrasting
confidence: 84%
“…The cosmic ray record at Earth is consistent with this picture such that only the first two shock-associated cosmic ray decreases had the signature expected for intercepting ejecta material. This same time period was also examined by Bavassano et al (1994). However, we do not agree with their conclusion that "magnetic clouds" extending at least 75 ø from the source longitude were present.…”
contrasting
confidence: 84%
“…This effect was analyzed recently, both theoretically (Dorman et al, 1995) and experimentally on the basis of the network of CR stations (Belov et al, 1995a,b). The predecrease effect can be due to a magnetic connection of the Earth with regions (moving from the Sun) with reduced CR density; this lower density can be observed at the Earth along the actual direction of IMF lines (Nagashima et al, 1990;Bavassano et al, 1994); 3. CR fluctuations: Many authors found some peculiarities in the behavior of CR fluctuations before FD: changes in frequency spectrum; appearance of peaks in spectrum at some frequencies; variations in some special parameter introduced for characterizing the variability of fluctuations.…”
Section: And 2)mentioning
confidence: 99%
“…According to Cane and Richardson, there was another shock passing the Earth as early as 09:16 UT, but that was suggested to be related to one of the Ha or X-ray¯ares at the Sun which preceded the large 19 October¯are. However, Bavassano et al (1994) relate the ®rst shock to the 19 October¯are. Direct evidence of ejecta from the 22 October event was not observed, because IMP 8 was in the magnetosphere, but their passage was considered to be plausible by Cane and Richardson (1995).…”
Section: Observationsmentioning
confidence: 99%
“…On 26 October, the shock produced by the last CME was seen as an SC, too, but Cane and Richardson concluded that the ejecta from this event did not pass the Earth. Bavassano et al (1994) state that the trapping eect of these ejecta is`marginally``seen'' by cosmic rays'.…”
Section: Observationsmentioning
confidence: 99%